2019
DOI: 10.9734/ajopacs/2019/v7i230092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties of a New (Polymer and Chalcone)

Abstract: This paper included two objectives: (i) Synthesis of Polymer {poly 2- [1- phenyl -3-(4-methyl phenyl)-4, 5-dihydropyrazole-5-yl-(4-phenoxy carbonyl)] styrene} PMDPCS and structure characterized by FT-IR, 1H-NMR spectra and Uv/Vis and XRD. (ii) Synthesis of chalcone {3-(4-(dimethylamino) phenyl)-2-phenyl-(2E) propen-1-one} (DAPPP) for absorption and fluorescence spectra under different solvents and concentrations.  Also, under various concentrations, organic solvents and pump pulse energies of Nd: YAG laser, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The above results have been compared with the spectral properties of 3-(4-(dimethyl amino) phenyl)-1phenyl-(2E)-propen-1-one (DAPPP) as a reference dye [3]. the absorption and uorescence spectra of DAPPP in acetone for different concentrations ranging from 0.65 to 6.5mM.…”
Section: Fluorescence Of Mspppmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results have been compared with the spectral properties of 3-(4-(dimethyl amino) phenyl)-1phenyl-(2E)-propen-1-one (DAPPP) as a reference dye [3]. the absorption and uorescence spectra of DAPPP in acetone for different concentrations ranging from 0.65 to 6.5mM.…”
Section: Fluorescence Of Mspppmentioning
confidence: 99%
“…In the past few decades, studies on photophysical properties of organic uorescent compounds have been a subject of intensive investigation due to their increasing application in electronic and optoelectronic devices, biomedical imaging, and uorescence sensors [1][2][3][4][5]. The dye lasers based on rhodamine and coumarin derivatives are excellent laser media, but they have some shortcomings, such as a lack of photochemical stability [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the photophysical properties depending on solvent environment and the influence of the FGs have not been fully studied. In earlier study, we showed that 3-(4-(dimethyl amino) phenyl) -2phenyl-(2E) -propen -1-one (C1) produced ASE under pulsed Nd: YAG laser excitation at 532 nm [14]. The result revealed that C1 has a large Stokes shift, an excellent photo stability, and high intensity lasing action (Scheme1).…”
Section: Introductionmentioning
confidence: 98%
“…In the past few decades, studies on photophysical properties of organic fluorescent compounds have been a subject of intensive investigation due to their increasing application in electronic and optoelectronic devices, biomedical imaging, and fluorescence sensors [1][2][3][4][5]. Chalcone derivatives are extensively used in optoelectronic fields such as photorefractive polymers [6], nonlinear materials [7], chromophore sensors [8], and in the study of photo-alignment layer of liquid crystal displays [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcone derivatives have a functionality of a carbonyl group in conjugation with a carbon-carbon double bond, which is known as α, β-unsaturated keto group. The desirable properties of the chalcones are: adding/removing donor can modify high conjugation level; and the photophysical characteristics of these chalcones or acceptor groups the skeleton [13,14]. The doping of ZnO with other materials (heterostructures) has attracted significant interests from their predominant properties to combine two kinds of materials with lower photoexcitation threshold than individual components and decrease the recombination rate of electron-hole pairs by their physically separated band gap [15,16].…”
Section: Introductionmentioning
confidence: 99%